2018
DOI: 10.1371/journal.pgen.1007366
|View full text |Cite
|
Sign up to set email alerts
|

The ARE-binding protein Tristetraprolin (TTP) is a novel target and mediator of calcineurin tumor suppressing function in the skin

Abstract: An increased incidence of skin inflammatory diseases is frequently observed in organtransplanted patients being treated with calcineurin inhibitor-based immunosuppressive agents. The mechanism of increased skin inflammation in this context has however not yet been clarified. Here we report an increased inflammation following inhibition of calcineurin signaling seen in both chemically induced mouse skin tumors and in tumors grafted from H-rasV12 expressing primary human keratinocytes (HKCs). Following UVB or TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…As previously demonstrated in the context of imiquimod-induced dermatitis ( 11 ), dysregulated production of TNF in the absence of TTP in epidermal cells was responsible for increased expression of inflammatory mediators and recruitment of innate immune cells during carcinogenesis; conversely, regulated TTP overexpression resulted in decreased skin infiltration of immune cells in this model ( 13 ). Wu et al ( 32 ) reported that calcineurin inhibitors downregulate TTP expression in keratinocytes. In line with our data, this led to increased expression of inflammatory mediators in HRas V12 -transformed keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…As previously demonstrated in the context of imiquimod-induced dermatitis ( 11 ), dysregulated production of TNF in the absence of TTP in epidermal cells was responsible for increased expression of inflammatory mediators and recruitment of innate immune cells during carcinogenesis; conversely, regulated TTP overexpression resulted in decreased skin infiltration of immune cells in this model ( 13 ). Wu et al ( 32 ) reported that calcineurin inhibitors downregulate TTP expression in keratinocytes. In line with our data, this led to increased expression of inflammatory mediators in HRas V12 -transformed keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The application of stem cells, which are cells with high potential to proliferate and differentiate, has been proven to play essential roles in the regeneration of skin structures both in in vitro skin models and in in vivo wound healing [ 38 , 41 ], and more recently, an entire hair-bearing human skin was generated in organoids using embryonic stem cells [ 42 ]. Therefore, skin progenitor cells, including scalp-derived dermal progenitor cells and epidermal stem cells, which were prepared in our laboratory and have already been shown to possess the capacity to generate full-thickness skin containing skin appendages, including hair follicles and sebaceous glands [ 15 , 22 , 29 , 31 ], were used to reconstitute bilayer TESSs in the present study. TESSs collected at early-stage (day 5 and day 9) and at late-stage (day 14 and day 21) were grafted on full-thickness wound areas of mouse dorsal skin to cover the wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The grafted tissues were collected at the desired times and were fixed with 4% paraformaldehyde (PFA), then were embedded in paraffin blocks. Six-micrometer sections of paraffin-embedded tissues were made for H&E staining, IHC, and IF analyses following standard protocols [30][31][32]. The following staining kits were used according to the manufacturers' supplied protocols: an Alcian blue-Periodic Acid Schiff (PAS) stain kit (Cat.…”
Section: Hematoxylin and Eosin Immunohistochemistry And Immunofluormentioning
confidence: 99%
“…All TSCC cell lines, including Cal 27, SCC-9, SCC-25 and SCC-4 were purchased from the ATCC (Manassas, VA, USA). SCCO22 was derived from our previous publication[ 58 ]. All cells were grown in DMEM (Thermo Fisher Scientific, Waltham, MA, USA, #11965118) medium containing 10% fetal bovine serum (Biological Industries, Kibbutz Beit Haemek, Israel, #1809249),100 IU/ml penicillin and 100 mg/ml streptomycin (Thermo Fisher Scientific, #1935444).…”
Section: Methodsmentioning
confidence: 99%